Percutaneous transluminal coronary angioplasty (PTCA): Attention on imperative facet - Abraham Titus, Siby; Karadkar, Gargee (Indian Journal of Nursing Sciences, 2024)
Percutaneous Transluminal Coronary Angioplasty (PTCA) introduced in late 90s and is a relatively new form of treatment for coronary artery stenosis. The PTCA is associated with complications like hypotension secondary to the artery occlusion may cause a decrease of the flow in the other coronary arteries, leading to cardiogenic shock. Such serious problems are necessary to note and resolve immediately. It is very commonly found that the quality of life of people with PTCA procedure (instead of operation) three months after procedure is reduced. Further, it is required during and especially after procedure; this period the patient treatment team supports his family and puts under the necessary training (by physician and nurses) in this period to give appropriate care to patients and encourage them to pursue their condition in better way. Nurses play a strong role in helping patients reduce their risk for disease and make informed lifestyle changes. Importantly, knowledge about quality of life and rehabilitation is well understood by various recent studies on self-instructional module. This is further supported by fact that; self instructional module on post PTCA home care among patients was found to be effective and helped the patients to improve their knowledge about post PTCA home care. Also analysis revealed a very high association between knowledge score with age, gender, education, occupation and income, which further help the patients to increase knowledge and improve the quality of life. This review concentrates mainly in the Percutaneous Transluminal Coronary Angioplasty and related complications, rehabilitation along with the Self-instructional modules (SIM).